Encryption Based Access Control Model In Cloud: A Survey - Rachana Chavda; Rajanikanth Aluvalu (Universitas Islam Sultan Agung, 2015)
Cloud computing is known as “Utility”. Cloud Computing enabling users to remotely store their data in a server and provide services on-demand. Since this new computing technology requires user to entrust their valuable data to cloud providers, there have been increasing security and privacy concerns on outsourced data. We can increase security on access of the data in the cloud. Morever we can provide encryption on the data so third party can not use thedata. In this paper we will be reviewing various encryption based access control model for enhancing cloud security along with their limitations. We will be concluding with a proposed access control model to enhance cloud security.